Presence of Cystic Artery in the Calots Triangle and Its Relation with Common Hepatic Duct a Postmortem Study (Bangladesh Journal of Anatomy, 2013)
Introduction: Most common disease of liver and biliary tree is cholelithiasis which needs surgical intervention. Safe execution of traditional cholecystectomy or laparoscopic surgery needs proper knowledge of the origin, course, branching pattern of the cystic artery and its relation with common hepatic duct. This study was aimed to find the presence of cystic artery in the Calots triangle and its relation with common hepatic duct to prevent any iatrogenic complications especially for newer surgeons in this field. Materials and Methods: This study was done on 60 postmortem gallbladder collected from postmortem dead bodies under the guidance of Forensic Medicine department of Rangpur Medical College, Rangpur. After collection of the specimen, the boundary of the Calot triangle was identified and course of the cystic artery was observed whether it was passing through the triangle or not. The relation of the cystic artery with the common hepatic duct was also noticed. Results: It was found from the result of the present study that out of 60 cases cystic artery was found as a content of Calots triangle in 58 (96.65%) cases. Regarding the relations of the cystic artery, out of 60 specimens, in 54 cases (90%) cystic arteries were observed to pass behind the common hepatic duct. In four cases (6.67%) cystic artery were found crossing over the common hepatic duct and in two cases (3.33%), cystic artery were found crossing below the cystic duct. In one cases, branches of cystic artery (superficial and deep branch) was found. In every specimen a Calots node was found within the Calots triangle. Discussions: The result of the present study was compared with other workers. Though many of the workers found similar results regarding the course of the cystic artery through the Calot triangle but some workers found higher number of cystic artery passing outside the triangle. Also higher percentage of cystic artery passing over the common hepatic duct was found by many workers than the present study. DOI: http://dx.doi.org/10.3329/bja.v10i2.17282 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 50-56